Psychological restoration depends on curiosity, motivation, and species richness during a guided bird walk in a suburban blue space - Randler, Christoph; Vanhöfen, Janina; Härtel, Talia; Neunhoeffer, Freya; Engeser, Cheyenne; Fischer, Christian (Frontiers in Psychology, 2023)
Urban and suburban green and blue spaces are important places for human recreation, and the impact of biodiversity on psychological and recalled restoration has received much attention. This study addresses the relationship between bird species richness and restoration in a controlled field experiment (guided bird walk) applying a battery of individual trait scales (need for cognition, personality) as predictors of restoration. We found a significant positive relationship between the number of bird species present and recalled restoration. Personality, bird species knowledge, bird related interest as test measures, demographics and birding specialization as self-report had no influence on psychological restoration. However, need for cognition correlated positively with psychological restoration, thus providing a new predictive variable. All subscales of the intrinsic motivation scale (enjoyment, perceived competence, perceived choice, pressure/tension) were positively correlated with restoration except of pressure/tension. Learning emotions like interest and well-being were positively related to restoration, while boredom was negatively related. Therefore, we suggest research to examine the restorative function of more cognitive-oriented programs because people may also need cognition when it comes to restoration. We also suggest a broader focus on education and cognitive aspects when it comes to linking biodiversity and health within the framework of ecosystem services.